2018
DOI: 10.1016/j.gendis.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The novel roles of circular RNAs in metabolic organs

Abstract: Circular RNAs (circRNAs) with a covalently closed loop structure which was different with linear RNAs, recently re-merged as novel regulator and exerted function in multiple biological processes. Through deep RNA sequencing (RNA-seq) technology coupled with bioinformatic analyses, a number of circRNAs has been identified. Moreover, circRNAs exhibit tissue- and development-specific expression indicating their potential biological significance. Actually, function of circRNAs as miRNA sponge has been well demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 90 publications
0
13
0
1
Order By: Relevance
“…Currently, it is generally accepted that the biogenesis of circRNAs is mainly produced through four different mechanisms: lariat‐driven circularization, intron pairing‐driven circularization, RBP binding‐driven circularization and the biogenesis of tricRNA (Zang, Lu, & Xu, 2020; Figure 1). The first model is lariat‐driven circularization path, which requires that an upstream 3′ splice site be joined to a downstream 5′ splice site resulting in exon skipping to form an RNA lariat consisting of several exons and introns (Zhang, Guo, & Li, 2018). Interestingly, ciRNAs biogenesis requires a key motif consisting of both a 7‐nt GU‐rich element close to the 5′ splice site and an 11‐nt C‐rich element near the branch point site (Tran et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, it is generally accepted that the biogenesis of circRNAs is mainly produced through four different mechanisms: lariat‐driven circularization, intron pairing‐driven circularization, RBP binding‐driven circularization and the biogenesis of tricRNA (Zang, Lu, & Xu, 2020; Figure 1). The first model is lariat‐driven circularization path, which requires that an upstream 3′ splice site be joined to a downstream 5′ splice site resulting in exon skipping to form an RNA lariat consisting of several exons and introns (Zhang, Guo, & Li, 2018). Interestingly, ciRNAs biogenesis requires a key motif consisting of both a 7‐nt GU‐rich element close to the 5′ splice site and an 11‐nt C‐rich element near the branch point site (Tran et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Very little information is available about the role of circRNAs in sepsis, because the elucidation of the role that these molecules play in human diseases has become relevant only in recent years. However, circRNAs may play a key role in sepsis because of their ability to modulate different molecular mechanisms [ 10 ], including inflammation [ 83 ] and immune response [ 62 ], and to control multiple biological processes in metabolic organs (i.e., liver, pancreas [ 84 ]) ( Figure 3 and Table 1 ). Moreover, the identification of the mechanism by which host circRNAs can bind viral mRNAs merits special attention, because it indicates that circRNAs are likely to resist viral infection [ 85 ] ( Figure 3 ).…”
Section: Circrnas Function In Sepsismentioning
confidence: 99%
“…The first study to confirm the presence of circRNAs in human cells by Nigro et al (1991) , reported the detection of circular transcripts derived from the tumor suppressor gene DCC in several human tumor cell lines. Recently, with the advent of new sequencing technologies, such as next-generation sequencing (NGS), a growing number of circRNAs have been reported ( Hanan et al, 2017 ; Wang et al, 2017 ; Zhang Z.-C. et al, 2018 ; Zaiou, 2019 ), and have now become a “hot topic.”…”
Section: Introductionmentioning
confidence: 99%